Виробництво піротехнічних порошків цирконію на Донецькому хіміко-металургійному заводі - Шпильовий, Леонід Вікторович (Національний технічний університет "Харківський політехнічний інститут", 2023)
In the conditions of the development of an independent state, there is a need for comprehensive research and rethinking of little-known pages of national history, including the history of industry. Among them, the history of individual enterprises, individual branches of industry, in particular, zirconium production, is relevant and insufficiently studied. Among the many fields of application of metallic zirconium, the use of its powders occupies a prominent place, primarily in pyrotechnics and ammunition production. The study of the history of the zirconium industry of Ukraine is also relevant in view of the need to draw the attention of government officials and the general public to production and technologies important for ensuring the country's defense capability. The first enterprise of the rare metal, in particular, zirconium industry of Ukraine, which organized the production of zirconium powders, was the Donetsk Chemical and Metallurgical Plant (DHMZ).

В умовах розбудови незалежної держави виникає потреба всебічного дослідження та переосмислення маловідомих сторінок вітчизняної історії, у тому числі історії промисловості. Серед них актуальною і недостатньо вивченою є історія окремих підприємств, окремих галузей промисловості, зокрема, виробництва цирконію. Серед багатьох галузей застосування металевого цирконію чільне місце займає використання його порошків, в першу чергу в піротехніці та виробництві боєприпасів. Дослідження історії цирконієвої промисловості України є актуальним ще й з огляду на необхідність привернути увагу урядовців та широкої громадськості до виробництв, технологій, важливих для забезпечення обороноздатності країни. Першим підприємством рідкіснометалічної, зокрема, цирконієвої промисловості України, на якому було організовано виробництво порошків цирконію, був Донецький хіміко-металургійний завод (ДХМЗ).
Production of Pyrotechnic Zirconium Powder at the Donetsk Chemical and Metallurgical Plant
Keywords: zirconium industry; history; Ukraine; zirconium powder; pyrotechnics; Donetsk chemical and metallurgical plant; цирконієва промисловість; історія; Україна; порошок цирконію; піротехніка; Донецький хіміко-металургійний завод